2016
DOI: 10.1109/jstars.2016.2606320
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Successional Stages and Cover Changes of Tropical Forest Based on Digital Surface Model Analysis

Abstract: Forests are in a permanent state of change due to natural and anthropogenic processes. Long-term time series analysis makes it possible to reconstruct the forest history and perform a multitemporal analysis on the cause and effect of changes. This paper describes an approach for successional stage classification in a tropical forest based on vertical structure variations. Stereophotogrammetry and novel image matching methods are used to produce dense digital surface models (DSMs) from optical images (historica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
1
19
0
3
Order By: Relevance
“…However, the mean error for Hst.dev of 0.5 m is similar or better compared to results of other studies using UAV-based photogrammetric point clouds in estimating tree height (Zarco-Tejada et al 2014, Zahawi et al 2015, Wallace et al 2016. Berveglieri et al (2016) used photogrammetric point clouds to derive information from vertical structure of Brazilian semideciduous tropical forest and concluded that it was possible to classify successional stage with this information. Based on also our results, the accuracy of height variation could be used for estimating biodiversity when assessed with vertical structure of a forest.…”
Section: Discussionsupporting
confidence: 77%
“…However, the mean error for Hst.dev of 0.5 m is similar or better compared to results of other studies using UAV-based photogrammetric point clouds in estimating tree height (Zarco-Tejada et al 2014, Zahawi et al 2015, Wallace et al 2016. Berveglieri et al (2016) used photogrammetric point clouds to derive information from vertical structure of Brazilian semideciduous tropical forest and concluded that it was possible to classify successional stage with this information. Based on also our results, the accuracy of height variation could be used for estimating biodiversity when assessed with vertical structure of a forest.…”
Section: Discussionsupporting
confidence: 77%
“…A professional drone (hexacopter with Tarot 960 foldable frame) equipped with a hyperspectral camera based on Fabry-Pérot interferometer (UAV FPI) and a good quality Samsung NX500 RGB camera (UAV RGB) were used. Different versions of this light-weight FPI hyperspectral camera (Saari et al, 2011;Oliveira et al, 2016a) have showed potential in both agriculture Kaivosoja et al, 2013) and other vegetation mapping tasks (Näsi et al, 2015;Berveglieri et al, 2016;Moriya et al, 2017;Nevalainen et al, 2017). In this study, FPI2012b sensor was configured with 36 spectral bands in 500 nm to 900 nm spectral range.…”
Section: Remote Sensing Data Setsmentioning
confidence: 99%
“…Photogrammetric point clouds were used to derive information from vertical structure of Brazilian semideciduous tropical forest in [74], and they concluded that it was possible to classify successional stage with this information. Our results support their findings.…”
Section: Discussionmentioning
confidence: 99%